Unexpected impacts of the Tropical Pacific array on reanalysis surface meteorology and heat fluxes. Issue 17 (3rd September 2014) - Josey, S. A.; Yu, L.; Gulev, S.; Jin, X.; Tilinina, N.; Barnier, B.; Brodeau, L.
Abstract The Tropical Pacific mooring array has been a key component of the climate observing system since the early 1990s. We identify a pattern of strong near surface humidity anomalies, colocated with the array, in the widely used European Center for Medium Range Weather Forecasting Interim atmospheric reanalysis. The pattern generates large, previously unrecognized latent and net air‐sea heat flux anomalies, up to 50 Wm−2 in the annual mean, in reanalysis derived data sets employed for climate studies (TropFlux) and ocean model forcing (the Drakkar Forcing Set). As a consequence, uncertainty in Tropical Pacific ocean heat uptake between the 1990s and early 2000s at the mooring sites is significant with mooring colocated differences in decadally averaged ocean heat uptake as large as 20 Wm−2. Furthermore, these results have major implications for the dual use of air‐sea flux buoys as reference sites and sources of assimilation data that are discussed.